PTU-041 Sub-squamous Columnar Neoplasia After Successful Radiofrequency Ablation For Barrett's Related Neoplasia Is Rare But Highlights Requirement For Long Term Follow Up In These Patients. (9th June 2014) - Haidry, RJ; Banks, M; Gupta, A; Butt, M; Rodriguez-Justo, M; Novelli, M; Lovat, L
Abstract : Introduction: Radiofrequency ablation (RFA) combined with endoscopic mucosal resection (EMR) has become the preferred treatment for BE related neoplasia. Success rates of 90% after treatment with a durability of up to 95% at 5 years are reported. The development of sub-squamous intestinal metaplasia (IM) after successful RFA is recognised and has been reported to range from 0–30%. It's clinical significance remains unclear. However the development of sub-squamous neoplasia after successful treatment is limited to only a few cases world wide in the literature. Methods: We prospectively examine the incidence of sub-squamous neoplasia after successful RFA from one of the UKs largest academic tertiary centres for patients undergoing RFA for BE neoplasia between 2008–2013 at University College Hospital, London. Before RFA, visible lesions and nodularity were entirely removed by EMR. Thereafter patients underwent RFA every 3 months until all visible BE was ablated. Biopsies were taken at 12 months. After successful treatment patients were followed up 3 monthly for the first year, at 6 month intervals for the second year and annually thereafter. Biopsies were taken from 1cm below the neo z-line and from the previously treated BE segment using the Seattle protocol. Enhanced imaging endoscopic imaging was used in all cases. Results: At our institution 197 patients have undergone RFA since 2007 of which 145 have completed treatment. Eighty percent of patients (116/145) achieved CR-D at 12 months. At 5 years 90% of patients remain disease free (median follow up 20 months, IQR 9 -32). There have been a total of 11 recurrences after successful RFA (median time to recurrence – 380 days, IQR 150–884). Four of these patients had sub-squamous high grade glandular dysplasia (HGD). All had had confirmed eradication of dysplasia and IM after the 12 month end of protocol biopsy. These sub-squamous recurrences occurred at 3, 7, 13 and 36 months respectively after eradication was confirmed. One of the four patients was found to have buried HGD on biopsy at the neo z-line and the area was subsequently treated with EMR. The other 3 cases developed visible lesions in neo-squamous mucosa proximal to the neo z-line. All were removed successfully with EMR and demonstrated buried HGD. All 4 cases remain in follow up with no neoplasia at most recent biopsy. Conclusion: Although rare, buried neoplasia after successful eradication with RFA can occur. Identification of these cases indicates the need for continued and vigilant surveillance following RFA, even after complete eradication of IM. Early recognition of recurrence can lead to treatment at an early stage. Disclosure of Interest: None Declared.